Comparative analysis of perceived stress in females with and without polycystic ovary syndrome - Khan, Sher Afghan; Khan, Muhammad Junaid; Khan, Faisal; Nawaz, Qadeer; Ahmed, Sameer; Zaman, Masud Uz (International Journal of Pathology, 2025)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine diseases in females of reproductive age group. It is a complicated endocrine disorder that has many adverse effects on female’s physical and mental health. Polycystic ovary syndrome is characterized by many metabolic, endocrine, reproductive and psychological effects. Recently, the importance of stress with the concurrence of PCOS association has come into picture. Hence, this study was planned to find any significant relation between Perceived Stress Scale (PSS-10) between PCOS and healthy controls. Method: A total of 262 females were included in the study of which 140 females were the patients of PCOS and the remaining 112 were not suffering from PCOS. The data was analyzed using the Perceived Stress Scale (PSS), a globally recognized and widely utilized tool for assessing stress perception. The PSS has consistently demonstrated excellent reliability and validity, providing valuable insights into the relationship between perceived stress and various pathological conditions. Results: The results show that 71 (47%) of females were suffering from severe depression with PCOS while 51 (34%) were suffering from moderate depression and 28 (18%) were suffering from mild depression. Conclusion: It signifies that stress plays a vital role in the progress and management of PCOS and its complications.